Emergency Closed Reduction of a C4/5 Fracture Dislocation with Complete Paraplegia Resulting in Profound Neurologic Recovery. (12th September 2013) - Müller, Christian W.; Decker, Sebastian; Thietje, Roland; Krettek, Christian
Abstract : Introduction . Cervical spinal cord injuries due to traumatic fractures are associated with persistent neurological deficits. Although clinical evidence is weak, early decompression, defined as <24–72 h, has been frequently proposed. Animal studies show better outcomes after early decompression within one hour or less, which can hardly ever be achieved in clinical practice. Case Presentation . A 37-year-old patient was hospitalized after being hit by a shying horse. After diagnosis of C4/5 fracture dislocation and complete paraplegia, she was intubated and sedated with deep relaxation. Emergency reduction was performed at approximately 120 minutes after trauma. Subsequently, a standard anterior decompression, discectomy, and fusion were carried out. She was then transferred to a specialized rehabilitation hospital. Her neurologic function improved from AIS grade A on admission to grade B postoperatively and grade D after four months of rehabilitation. One year after the accident, she was ambulatory without walking aids and restarted horse riding. Discussion and Conclusion . Rarely in clinical practice, decompression of the spine canal can be performed as early as in this case. This case highlights the potential benefit of utmost early reduction in cervical fracture dislocations with compression of the spinal cord.